Effects of Cooperative Loan on the Cattle Marketing in Ogun State, Nigeria: Array - Akerele, Ezekiel Olaoluwa (Acta Universitatis Danubius. Œconomica, 2022)
This study examined the effect of cooperative society loan on the cattle rearing and marketing in Ogun State, Nigeria. Specifically the study described the socio-economic characteristics of the respondents; examined the cost and returns to cattle marketing, analyze the effect of cooperative on returns to cattle marketing and identified the problem encountered in cattle marketing. A total of fifty (50) well-structured research questionnaires were administered among cattle marketers in the area, but forty seven (47) were returns good and used for analysis. The data generated were analyzed using descriptive and inferential statistics. The result revealed that majority of the respondents, constituting about 68.0% fall within the active age range of 31-50 years with the average age of the respondents was 45 years. Majority (89.4%) of the respondents had at least one form of education or the other, and majority (89.4%) of respondents are membership of cattle marketing association. The total revenue for cattle marketing was N1,297,430.56 while the total marketing cost was N1,071,391.84 representing 60.36% of the total revenue. The marketing efficiency index of the cattle marketers was 1.21%. This value is well above 100%, implying that the revenue generated from cattle by the marketers is sufficient to offset all costs with reasonable proportion as profit margin. The net income was significantly influenced by age, marital status, years of formal education and amount of loan borrowed. It is however experiencing major setbacks, for instance, price fluctuation and high cost of transportation. It is therefore recommended that youths should be encouraged to participate in marketing activities to expand the current marketing system and to address the challenges facing agriculture in term of food insecurity and revenue generation.